INTEGRATED HYDROBIOLOGICAL AND HYDROCHEMICAL ASSESSMENT OF RESERVOIR ECOSYSTEMS USING MULTIMETRIC ECOLOGICAL INDICES AND STATISTICAL MODELING APPROACHES (International Congress on Economics, Management and Business Studies, 2026)
This study presents an integrated hydrobiological and hydrochemical assessment of reservoir ecosystems in Uzbekistan using multimetric ecological indices and statistical modeling approaches. Physicochemical parameters, including water temperature, dissolved oxygen (DO), pH, mineralization, and nitrogen compounds, were analyzed alongside phytoplankton and zooplankton community structure.
Keywords: Reservoir ecology; hydrochemistry; Shannon index; Water Quality Index; ANOVA; zooplankton; phytoplankton; Uzbekistan.